Orchid conservation in the Americas - lessons learned in Florida - Stewart, Scott; Kane, Michael (Lankesteriana: International Journal on Orchidology, 2015)
Conservation can be a difficult concept to define, let alone apply. For some, plant conservation can simply mean the survey and cataloging of plant diver- sity within a defined conservation area. Others may define plant conservation as the collection and propa- gation of germplasm from one, or many, areas within a species’ range.